PENGARUH KOMUNIKASI INTERNAL DAN DISIPLIN KERJA TERHADAP KINERJA KARYAWAN PADA PT. INDOMARCO PRISMATAMA CABANG BALI - Katerina Dewi Ramadani; I Made Yudi Darmita; Laras Oktaviani (Universitas Triatma Mulya, 2023)
This study aims to determine and analyze the effect of internal communication and work discipline on employee performance at PT. Indomarco Prismatama Bali Branch. The sampling technique used in this study is Proportionate Stratified Random Sampling because it has members who are not homogeneous and proportionally stratified. The data collection technique used was a questionnaire distributed to 76 respondents. The analysis techniques in this study were descriptive analysis, validity and reliability tests, classic assumption tests, multiple linear regression tests, t-test analysis, and dominance/contribution tests (coefficient beta). Multiple linear regression analysis using SPSS 26 for windows software. The results of this study indicate that: Internal communication (X1) has a partially positive and significant effect on employee performance (Y) at PT. Indomarco Prismatama Bali Branch. Work discipline (X2) has a positive and significant effect partially on employee performance (Y) at PT. Indomarco Prismatama Bali Branch. Internal communication variable (X1) has a dominant influence of 0.414 on employee performance (Y) at PT. Indomarco Prismatama Bali Branch, because it has a larger value of standardized coefficients beta. The implication of this research is that the company is expected to pay close attention to internal communication and employee work discipline in order to improve employee performance at the company in the future.